'A River with a City Problem, not a City with a River Problem': Brisbane and its Flood-Prone River. (1st November 2018) - Cook, Margaret Helen
Abstract : This article explores the relationship between the Brisbane River and its river-plain dwelling citizens between 1824 and 1900 through four distinctive narratives. The first is praise for the river for its economic and utilitarian potential until severe flooding in 1893 prompts a second response of incredulity, followed by a third viewpoint demanding engineering solutions to tame nature to prevent future floods. A fourth subordinate voice appeared as an undercurrent to the demands to control nature, reflecting a burgeoning realisation that human action had created the flood hazard. Settlers had created a problem for both the river and the city. I argue that despite the accumulation of flood experience and climatic knowledge, prospective actions have evolved little since the initial British settlement in 1824.